Ewidencja i wycena portfela obligacji o oprocentowaniu stałym (inwestycja długoterminowa) sfinansowanych wyemitowanymi obligacjami o oprocentowaniu stałym według Międzynarodowych Standardów Sprawozdawczości Finansowej - Ryba, Adrian (Disclosure and Valuation of Fixed Income Bonds Portfolio (Long-Term Investment) Finances by Issue of Fixed Income Bonds on the Basis of International Accounting Standards, 2007)
This article describes "Fair Value Option" amendment, which has been added to International Accounting Standard no 39. IAS no 39 (before the introduction of this amendment) permitted any financial assets (except financial assets whose fair value is not verifiable) to be measured at fair value, but liabilities that are contractually related to their standard required to be measured at amortised cost. In this case the use of the "Fair Value Option" avoids reporting the volatility that would arise if the assets were measured at fair value and the offsetting liabilities were measured at amortised cost - in consequence only matched positions (for example long-term fixed income bonds portfolio finances by issue of fixed income bonds) are recognized in the same way (at fair value). Therefore the influence of financial instruments valuation (at fair value) on profit is presently limited.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1158, s. 280-286